Pemetaan Perubahan Tutupan Lahan Dengan Metode Supervised Classification Menggunakan Citra Landsat 8-9 di Kecamatan Sepaku Tahun 2014 dan 2024 - Musdalifah Musdalifah; Andi Baso Sofyan A. P.; Dyah Widyasasi; Romansah Wumu; Siti Hutami Adianengsih Gaffar (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2024)
This research is motivated by the relocation of the capital city from DKI Jakarta Province to East Kalimantan Province, specifically in the Sepaku Sub-district, Penajam Paser Utara Regency. The relocation of the capital city may lead to changes in land cover due to land conversion and development activities. The purpose of this study is to analyze changes in land cover in the Sepaku Sub-district, Penajam Paser Utara Regency, based on mapping using the supervised classification method with Landsat 8-9 imagery from 2014 and 2024. The results of land cover identification in the Sepaku Sub-district classify the area into vegetated areas (agriculture), vegetated areas (non-agriculture), open land, settlement and related land, and water bodies. In 2014, land cover in Sepaku Sub-district was dominated by non-agricultural vegetated areas, accounting for 60.04% of the total area, which slightly increased to 60.21% in 2024. Furthermore, the results show a slight increase in non-agricultural vegetated areas, from 75,804.1 hectares in 2014 to 76,013 hectares in 2024. Conversely, a decrease was observed in agricultural vegetated areas and open land types. The area of agricultural vegetated land decreased from 39,663 hectares in 2014 to 38,271 hectares in 2024, while open land decreased from 7,111 hectares in 2014 to 6,141.2 hectares in 2024. Meanwhile, settlement and related land cover experienced a significant increase, growing from 2,454 hectares in 2014 to 4,520.2 hectares in 2024.